2014
DOI: 10.3906/sag-1306-71
|View full text |Cite
|
Sign up to set email alerts
|

The McGrath Series 5 video laryngoscope versus the Macintosh laryngoscope: a randomized trial in obstetric patients

Abstract: The utilisation of whey is very important for preventing the waste of a protein-and lactose-rich dairy by product and protecting the environment. Therefore, the objective of this study was to investigate the effect of whey use in tel (wire) kadayıf (a Turkish dessert raw material) production on microbiological and technological properties and sensory characteristics of tel kadayıf. For this purpose, 3 experimental tel kadayıf samples were produced using different amounts (0%, 25%, and 50%) of fresh whey instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…The remaining 61 studies took place in the hospital operating theatre setting with elective surgical participants. Two studies specified inclusion of only obese participants, 21 23 one study included only obstetric participants, 25 one study only participants with untreated hypertension, 35 and one study only participants from the burns unit. 82 We included three studies that used a double-lumen tracheal tube for intubation.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The remaining 61 studies took place in the hospital operating theatre setting with elective surgical participants. Two studies specified inclusion of only obese participants, 21 23 one study included only obstetric participants, 25 one study only participants with untreated hypertension, 35 and one study only participants from the burns unit. 82 We included three studies that used a double-lumen tracheal tube for intubation.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…They found no difference regarding intubation times between the McGrath VL and the Macintosh DL. Arıcı et al [11] also found an increment in intubation times with the McGrath VL in their study with obese pregnant women. In this study, although the glottic image was better and the anaesthesiologist had experience with the McGrath VL, we found a longer duration of the intubation period in Group V. Another aspect, when compared with the Macintosh, was that a gum elastic bougie is needed more frequently for intubation with the McGrath VL [18].…”
Section: Discussionmentioning
confidence: 71%
“…Currently, they are stocked in 90% of obstetric units in the UK [12]. In obstetric practice, videolaryngoscopes have been used at elective caesarean section, in morbidly obese patients and during failed intubation [116][117][118][119][120][121][122][123][124][125]. However, currently there are no comparative studies of the best videolaryngoscope for the obstetric population [126].…”
Section: First Intubation Attemptmentioning
confidence: 99%